Bromatological characteristics of raw coffee beans marketed in Jaru-RO (Research, Society and Development, 2022)
The coffee beverage is one of the most important commodities, being appreciated all over the world, whose quality is influenced by several factors, both environmental and related to processing processes, highlighting here the roasting. Thus, the objective of this study was to evaluate coffees of two species (Coffea arábica and Coffea canephora) marketed in the form of raw beans in the municipality of Jaru-RO, submitted to different roasting profiles (light, medium and dark), in order to quantify the contents of aqueous extract, total ash, pH, total titratable acidity (TTA) and total proteins. The results showed that the only parameter that did not change during the roasting process between the species was total proteins, the others varied significantly, so that the values ​​of aqueous extract, total ash and pH increased with the roasting process, differently from ATT, since the dark roast promoted a lower value for this parameter. Therefore, it is possible to confirm that the roasting process interferes in the chemical composition of the coffee bean, and, consequently, in the quality of the beverage, and that this change is evident for both C. arabica and C. canephora coffees.